IKAN AIR TAWAR DI SUNGAI BATANG MUAR DESA SERAMI KABUPATEN MUKOMUKO - Peby Soraya; Cindy Eka Putri; Prisca Agustina Lestari; Erik Perdana Putra (Jurnal Biosilampari : Jurnal Biologi, 2021)
This study aimed to look at the inventory of freshwater fish species in the Batang Muar River, Serami Baru Village, Mukomuko Regency, Bengkulu. This study uses an exploratory descriptive research method by using a survey technique conducted by determining the point of observation. Determination of the location of the research is done by the method of purposive sampling. The samples obtained were grouped based on the same morphological characteristics and the number of each type was counted. Based on the results of the research, the results of the inventory of freshwater fish species in the Batang Muar River found 9 species consist of Oxyeleotris marmota, Angulia marmorata, Monopterus albus, Tor putitora, Labiobarbus leptocheilus, Mystacoleucus padanggensis, Osteochiolus vittatus, Chana striata and Schismatgobius ridawatiae.